2020
DOI: 10.1186/s12889-020-09397-8
|View full text |Cite
|
Sign up to set email alerts
|

The burden of disease and the cost of illness attributable to child maltreatment in Japan: long-term health consequences largely matter

Abstract: Background: Child maltreatment leads to enormous adverse short-and long-term health outcomes. The aim of this study is to estimate the burden of disease and the cost of illness attributable to child maltreatment in Japan. Methods: An incidence-based top-down cost of illness analysis was conducted to estimate medical costs and burden of disease attributable to child maltreatment based on a societal perspective. The assessment included short-term and long-term medical costs and burden of disease measured by Disa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…The remarkable differences highlighted by this analysis cast doubts on the reliability of estimates obtained by valuing the monetary burden from simple analyses based on DALYs and GDP per capita, a methodology widely used not only for cancer [13] but also in many other sectors such as infectious disease [54], injuries [55] and maltreatment-related illnesses [56].…”
Section: Discussionmentioning
confidence: 96%
“…The remarkable differences highlighted by this analysis cast doubts on the reliability of estimates obtained by valuing the monetary burden from simple analyses based on DALYs and GDP per capita, a methodology widely used not only for cancer [13] but also in many other sectors such as infectious disease [54], injuries [55] and maltreatment-related illnesses [56].…”
Section: Discussionmentioning
confidence: 96%
“…Family violence (FV) is a global health problem with direct and indirect consequences on long-term economic and welfare costs ( Bellis et al, 2019 ; Mo et al, 2020 ; Peterson et al, 2018 ). The concept of FV is understood rather similarly across international research literature, although cultural issues associated with FV and the definitions of FV vary between countries and studies.…”
Section: Introductionmentioning
confidence: 99%
“…If left unaddressed, these consequences can extend beyond childhood into adolescence and can continue to have an impact throughout adulthood, including worrying ramifications for future parenting behaviours and health outcomes (Felitti et al, 1998;Isobel et al, 2019). Also, studies have shown that there are significant longer-term and sometimes lifetime costs that result from managing these impacts, which involve significant societal expenses, including those associated with service areas such as health, welfare, unemployment, child protection and care, crime, and accommodation (Moore et al, 2015;Jaffee et al, 2018;Mo et al, 2020: Conti et al, 2021.…”
Section: Introductionmentioning
confidence: 99%